Simultaneous Analysis of Anti-Hypertensive Drugs by RP-HPLC: An Overview - Katkale, Akshay; Fodase, Sagar; Pingle, Ashok; Dhikale, Ganesh; Waghmare, Pratik; Dhake, Deepak (Asian Journal of Pharmaceutical Research and Development, 2024)
High performance liquid chromatography (HPLC) is an important qualitative and quantitative technique, generally used for the estimation of pharmaceutical and biological samples. In now a day pharmaceutical market, many newer antihypertensive combination drugs are available to control hypertension as well as to keep society healthy and stress free. All presently available old drugs have frequent dosing produces various side effects. So, there is need to analyse such antihypertensive drugs. The aim of this review is to analysed such commonly used antihypertensive combination drugs by using reverse phase high performance liquid chromatography (RP-HPLC). Reversed-phase high-performance liquid chromatography (RP-HPLC) involves the separation of molecules on the basis of hydrophobicity. The separation depends on the hydrophobic binding of the solute molecule from the mobile phase to the immobilized hydrophobic ligands attached to the stationary phase. The drugs like Amlodipine besylate and Valsartan, Irbesartan and Hydrochlorothiazide, Atenolol and Chlorthalidone, Hydrochlorothiazide and Candesartan, Ramipril and Amlodipine, Hydrochlorothiazide and Enalapril, Quinapril and Hydrochlorothiazide etc. About fifteen combination drugs are analysed by using RP-HPLC. This review assists in appropriate selection of column, mobile phase, pH, flow rate, detector and form of such combination drugs.